2005
DOI: 10.4049/jimmunol.174.3.1405
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3+ T-bet+ Tumor-Specific Th1 Cells Colocalize with and Inhibit Development and Growth of Murine Neoplasms

Abstract: Although T cells infiltrate many types of murine and human neoplasms, in many instances tumor-specific cytotoxicity is not observed. Strategies to stimulate CTL-mediated antitumor immunity have included in vitro stimulation and/or genetic engineering of T cells, followed by adoptive transfer into tumor-bearing hosts. In this model of B cell lymphoma in SJL/J mice, we used Tim-3+ T-bet+ Th1 cells to facilitate the development of tumor-specific CTL. Tumor-specific Th1 cell lines were polarized with IL-12 during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Our preliminary study on membrane-bound Tim-3 revealed that the expression of Tim-3 in vivo by transfection with expression plasmid in the established mouse B16F1 melanoma induced partially regression of tumor and enhanced T cell response (our unpublished data), suggesting that the effect of Tim-3 on antitumor immunity is a positive one. These results were consistent with a more recent study in which the administration of Tim-3 ϩ Th1 cells facilitated the development of tumor-specific CTL, suggesting that Tim-3 ϩ Th1 cells could be used to induce host antitumor response and inhibit the development and growth of tumor (37). These data offer a new insight into the mechanism through which Tim-3 regulates immune response of T cells, and add an additional level of complexity to the current description of the role of Tim-3 in immunoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Our preliminary study on membrane-bound Tim-3 revealed that the expression of Tim-3 in vivo by transfection with expression plasmid in the established mouse B16F1 melanoma induced partially regression of tumor and enhanced T cell response (our unpublished data), suggesting that the effect of Tim-3 on antitumor immunity is a positive one. These results were consistent with a more recent study in which the administration of Tim-3 ϩ Th1 cells facilitated the development of tumor-specific CTL, suggesting that Tim-3 ϩ Th1 cells could be used to induce host antitumor response and inhibit the development and growth of tumor (37). These data offer a new insight into the mechanism through which Tim-3 regulates immune response of T cells, and add an additional level of complexity to the current description of the role of Tim-3 in immunoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Irradiated splenocytes (3000 rad) were pulsed with escalating doses of TRP-1 106-130 or 1 M of an irrelevant peptide (gp100 [25][26][27][28][29][30][31][32][33] ). In some experiments, different tumor cells lines (B16, B16 CIITA, MCA 205, and EL4) were used as target cells.…”
Section: Cytokine Release Assaysmentioning
confidence: 99%
“…17,18 Limited studies indicate that both subtypes elicit antitumor effects, 19-21 but the Th1-polarized cells, secreting IFN-␥ and capable of enhancing activity of cytotoxic CD8 ϩ lymphocytes, have traditionally been regarded as more efficient. [22][23][24][25] However, it is also clear that CD4 ϩ T regulatory cells (T regs ) can efficiently suppress the function of antitumor CD8 ϩ T cells. 5,[26][27][28] Recently, the novel Th17 lineage, generated in the presence of TGF-␤ and IL-6 and expanded under the influence of IL-23, [29][30][31] has been associated with responses against certain infections and implicated in the development of autoimmunity in animal models that had been previously linked to Th1-type responses (experimental autoimmune encephalitis, collagen-induced arthritis).…”
mentioning
confidence: 99%
“…IFN-␥ secreted by CD4 ϩ Th1 cells may have antitumor (12,14) or antiangiogenic effects (15). In contrast, CD4…”
mentioning
confidence: 99%